Detection and quantification of Verticillium dahliae and V. longisporum by droplet digital PCR versus quantitative real-time PCR - Wang, Di; Jiao, Xinya; Jia, Haijiang; Cheng, Shumei; Jin, Xi; Wang, Youhua; Gao, Yunhua; Su, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2022)
Vascular wilt, caused by Verticillium dahliae and V. longisporum, limits the quality and yield of agricultural crops. Although quantitative real-time PCR (qPCR) has greatly improved the diagnosis of these two pathogens over traditional, time-consuming isolation methods, the relatively poor detection sensitivity and high measurement bias for traceable matrix-rich samples need to be improved. Here, we thus developed a droplet digital PCR (ddPCR) assay for accurate, sensitive detection and quantification of V. dahliae and V. longisporum. We compared the analytical and diagnostic performance in detail of ddPCR and the corresponding qPCR assay against the genomic DNA (gDNA) of the two fungi from cultures and field samples. In our study, the species specificity, quantification linearity, analytical sensitivity, and measurement viability of the two methods were analyzed. The results indicated that ddPCR using field samples enhanced diagnostic sensitivity, decreased quantification bias, and indicated less susceptibility to inhibitors compared with qPCR. Although ddPCR was as sensitive as qPCR when using gDNA from cultures of V. dahliae and V. longisporum, its detection rates using field samples were much higher than those of qPCR, potentially due to the inhibition from residual matrix in the extracts. The results showed that digital PCR is more sensitive and accurate than qPCR for quantifying trace amounts of V. dahliae and V. longisporum and can facilitate management practices to limit or prevent their prevalence.